Microorganisms causing wound infection and their antibiotic susceptibility pattern - Swain, Bichitrananda; Samal, Debashish; Agrawal, Sujan Narayan (International Journal of Research in Medical Sciences, 2022)
Background: Pyogenic infection is one of major causes of morbidity and increasing medical expense. Multiple organisms can cause wound infection. Drug resistant bacteria are the most important therapeutic challenge. Methods: A prospective study was carried out from July 2021 to October 2021and pus samples were collected from suspected OPD and indoor patients with wound infection. The pus specimen after appropriate aerobic culture, the bacteria grown was identified by colony morphology, staining reaction and different standard biochemical tests. Modified Kirby Bauer disc diffusion method was used for the antimicrobial susceptibility testing. Results: Out of 140 pus samples from wound infection of suspected patients, 88 (62.9%) showed bacterial growth and most of them were from male patients, 66 (64.70%). Most of the isolates were isolated from in-patient (52, 59.1%). Staphylococcus aureus was the most prevalent pathogen (38.6%) followed by Klebsiella spp. (22.7%). Most of the S. aureus were MRSA (32.4%) and sensitive to vancomycin, linezolid and teicoplanin. Klebsiella spp. and other Gram-negative bacteria isolates were mostly sensitive to imipenem and they were highly resistant to co-trimoxazole, cephalosporins. Conclusions: The organisms mainly attributing for pyogenic wound infections are S. aureus, Klebsiella species. High level of drug resistance was seen for both Gram positive and Gram-negative bacteria. Continuous surveillance is necessary. As the microorganisms isolated were mostly resistant to different antibiotic classes, so effective surveillance and proper implementation of local antibiotic policy is needed.